A Meta-Analytic Review of Pretrial Research: Risk Assessment, Bond Type, and Interventions - Bechtel, Kristin (American journal of criminal justice, 2017)
This study makes an attempt to aggregate what we currently know about pretrial decision making and jurisdictions’ responses to the pretrial population. This meta-analysis began with an exhaustive search for pretrial research which may have revealed the most prominent finding—that being a distinct lack of research that utilizes any amount of methodological rigor. The findings of this meta-analysis hold several policy implications for the field of pretrial research and practice. First, future research studies in the field of pretrial need to focus on methodological quality and rigor. Second, it appears that some conditions of release may be related to a defendant’s likelihood of failure to appear. Third, it appears that none of the conditions of release reviewed in this study are related to a defendant’s likelihood of re-arrest while on pretrial release. Finally, it is recommended that the field of pretrial develop a sound research agenda and execute that plan with rigor, transparency, and an approach that favors the continued cumulation of knowledge. Strong conclusions about the impact of pretrial release conditions cannot be made as the quality of the pretrial research, overall, is weak at best.